Are we are equipped to handle an epidemic of chronic kidney diseases? - T. S., Selvavinayagam (International Journal Of Community Medicine And Public Health, 2017)
Background: The utilization pattern under Tamil Nadu state health insurance program, namely The Chief Minister’s Comprehensive Health Insurance Scheme (CMCHISTN) reveals that chronic kidney disease (CKD) is one of the high expenditure elements and this study explores need and availability of facilities to handle the CKD in the state. The objectives of the study were to estimate the requirement of renal replacement therapy (RRT) including haemodialysis and renal transplant surgery in the population; to compute the available facility and measure the shortfall if any, so as to create an evidence-based comprehensive strategy to handle CKD in Tamil Nadu. Methods: Based on the existing data, the estimated prevalence of CKD is calculated and it is matched with a utilization of services under CMCHISTN so as to arrive the requirements and gaps in RRT. Results: The existing system is able to cover only around 3% of the estimated population needing RRT and projected shortfall is around 68% in HD machines. Conclusions: The government needs to create RRT facility in the public sector covering both MHD and RT along with the suitable preventive strategy to reduce the risk factors and promote an early screening of diabetes and hypertension.